Impact of adjuvant trastuzumab therapy and its discontinuation on cardiac function and mortality in patients with early-stage breast cancer: An analysis based on the Japanese Receipt Claim Database - Keiko Miyazato; Hiroshi Ohtsu; Akihiko Shimomura; Naohiro Yonemoto; Chikako Shimizu; Kazuhiro Sase; Shinichiro Ueda (Breast)
Standard trastuzumab therapy can reduce the risk of early recurrence of HER2-positive breast cancer. However, trastuzumab-induced cardiac dysfunction may force the discontinuation of adjuvant trastuzumab therapy. Incidentally, there are still unclear whether or not trastuzumab treatment should be continued in the setting of reduced cardiac function. We aimed to investigate the association between trastuzumab discontinuation, the development of cardiac dysfunction during trastuzumab treatment, and all-cause mortality using the JMDC as the Japanese claims database. Between 2010 and 2019, 1779 women with early-stage breast cancer underwent surgery with adjuvant trastuzumab therapy (TZ). A 1:1 propensity score (PS) matching was conducted for patients who completed or discontinued TZ. The rates of cancer therapy-related-cardiovascular toxicity (CTR-CVT) and mortality in the TZ completion and discontinuation groups were compared. After PS matching, the TZ completion group (CMP_PSM: n = 83) and discontinuation group (INT_PSM: n = 83) were included in the study. TZ was administered for 12 and 5 months in CMP_PSM and INT_PSM, respectively. The cumulative incidence of CTR-CVT was significantly higher in CMP_PSM than INT_PSM (log-rank test, P = .0096). The mortality rate was significantly higher in INT_PSM than in CMP_PSM. The all-cause mortality in INT_PSM tended to increase at a constant rate after treatment, even after discontinuation. Our findings suggest that discontinuation of trastuzumab treatment worsens patient prognosis due to insufficient treatment of breast cancer rather than due to the cardiovascular toxicity of the drug.